Computational Fluid Dynamics Simulation of Steel Bars Cooling by Free Convection and Thermal Radiation - Terenzi Seixas, Paulo Henrique; Silva, Paul Campos Santana; Huebner, Rudolf (Applied Mechanics and Materials, 2015)
In this article, the pilling process of hot steel bars is analyzed. During the loading three bars are placed over a wood surface, after those other three are placed over the previous for two times with 5 minutes intervals between them.They are all subject to a slow cooling by thermal radiation and free convection.A Computational Fluid Dynamics (CFD) model to predict the temperature profile of them is developed. Comparison between the CFD simulation results and experimental data yielded an average difference in the bars temperature between -0.3oC and 3.5oC.